Accurate modelling of 3D-trench silicon sensor with enhanced timing performance and comparison with test beam measurements. (29th September 2021) - Brundu, D.; Cardini, A.; Cossu, G.M.; Dalla Betta, G.-F.; Garau, M.; Lai, A.; Lampis, A.; Loi, A.; Obertino, M.M.; Siddi, B.G.; Vecchi, S.
Abstract: This paper presents the detailed simulation of a double-pixel structure for charged particle detection based on the 3D-trench silicon sensor developed for the TIMESPOT project and a comparison of the simulation results with measurements performed at the π-M1 beam at PSI laboratory. The simulation is based on the combined use of several software tools (TCAD, GEANT4, TCoDe and TFBoost) which allow to fully design and simulate the device physics response in very short computational time, O(1–100 s) per simulated signal, by exploiting parallel computation using single or multi-thread processors. This allowed to produce large samples of simulated signals, perform detailed studies of the sensor characteristics and make precise comparisons with experimental results.